Decision-Making and Selection Framework for Potential Implementation of Concentrated Solar Power Technologies: Case Study - Maycon Figueira Magalhães; Boniface Dominick Mselle; Francisca Galindo (Energies)
The decarbonization of industrial processes requires efficient and scalable renewable energy solutions. Concentrated Solar Power (CSP) technology stands out by providing both electricity and high-temperature heat, yet its optimal deployment remains a challenge. This study presents an innovative framework for selecting and optimizing CSP technologies tailored for potential industrial practical applications. In this study, a multi-phase approach is deployed integrating a decision matrix, performance simulations using SOLARPILOT and SAM, and techno-economic evaluation to identify the best CSP solution. The study addresses the feasibility of four candidate CSP technologies, the characteristics of deployment areas, operation parameters such as energy storage time, and characteristics of energy storage material (comparing commercially available materials and an innovative molten salt named FERT-1). The results highlight solar towers as the most suitable technology, while the characteristics of the deployment can lead to over 3.2% difference in annual energy generation (when comparing between two areas, A1 and A2). Regarding energy storage, an optimal storage time of 11 h was identified, achieving a Levelized Cost of Electricity (LCOE) of 24–25 cents/kWh and a 31–32% energy capacity factor. Moreover, regarding energy storage material, the innovative molten salt highlighted improved thermal efficiency.